Study on a new shear wall system with shaking table test and finite element analysis. - Lu, Xilin
A new seismic energy dissipation shear wall structure is proposed in this paper. The new shear wall is one with purposely built in vertical slits within the wall panel, and rubber belts as seismic energy dissipation devices are installed in the vertical slits. In order to verify this concept, shaking table tests of a 10 storey shear wall model with rubber belts filled in the vertical slits were carried out, and comparison of seismic behaviour was made between the new shear wall system and a shear wall with reinforced concrete connecting beams as energy dissipation. Furthermore, the seismic behaviour of this new shear wall is analysed by a finite element time history analysis method. The test and analysis show that the new shear wall system has a very good ability to dissipate seismic energy and is easy to use in engineering practice.
Keywords: Reinforced concrete; Shear wall; Shaking table test; Seismic energy dissipation; Finite element method; Time history analysis